(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The research employs a qualitative analysis of Adiga’s selected novels, focusing on TheWhite Tiger and Last Man in Tower, as primary sources. Drawing from theories of social realism andglobalization, the study explores how Adiga’s narratives portray the lives of characters who navigate theintricacies of a globalized world. Despite India’s steady march to global superpower status, the WhiteTiger explores the irony of how the subaltern people are still being oppressed and exploited by theprivileged class of the society. The book focuses on the disparity between the parts of India that havebenefited from globalization and the expansion of the Indian economy and the other parts of India thathave not. To the contrary of what many would have you believe, none of the social problems that havebeen happening in the nation have been removed they have only been substituted. Rape of women,terrorism, political terrorism, corruption, and gambling have supplanted formerly dominant societalconcerns such as child marriage, dowry, sati, excessive work, and the denial of women’s education.